Impact of whey protein supplementation in a weight-loss intervention in rural dwelling adults: A feasibility study. (October 2021) - Batsis, John A.; Petersen, Curtis L.; Cook, Summer B.; Al-Nimr, Rima I.; Driesse, Tiffany; Pidgeon, Dawna; Fielding, Roger
Summary: Background & aims: Weight loss in older adults enhances physical function, but may lead to sarcopenia and osteoporosis. Whey protein is a low cost rich source of essential amino acids, may improve physical function. We evaluated the feasibility and acceptability of consuming whey protein in the context of a weight-loss intervention in older adults with obesity. Methods: A 12-week pilot feasibility, non-randomized weight loss study of 28 older adults was conducted, consisting of individualized, weekly dietitian visits with twice weekly physical therapist-led group strengthening classes. Half consumed whey protein, three times weekly, following exercise. Preliminary efficacy measures of body composition, sit-to-stand, 6-min walk and grip strength and subjective measures of self-reported health and function were also evaluated. Results: Of the 37 enrolled, 28 completed the study (50 % in the protein group). Attendance rates for protein vs. non-protein groups were 89.9 ± 11.1 % vs. 95.6 ± 3.4 % (p = 0.08). Protein consumption was high in those attending classes (90.3 %) as was compliance at home (82.6 %). Whey was pleasant (67.3 ± 22.1, range 30–100, above average), had little aftertaste, and was neither salty or sticky. All were compliant (0.64 ± 0.84, range 0–5, low = higher compliance). Both groups lost significant weight (protein vs. no protein, −3.45 ± 2.86 vs. −5.79 ± 3.08, p = 0.47); Sit-to-stand, 6-min walk, and gait speed were no different, grip strength was improved in the protein compared to the non-protein group (−2.63 kg vs. 4.29 kg; p < 0.001). Conclusions: Our results suggest that whey protein is a low-cost and readily available nutritional supplement that can be integrated into a weight loss intervention.